Efectivity of a Hybrid Classroom-Based Reflective Microlearning Model for Prospective Physics Teachers - Ariska, Melly; Akhsan, Hamdi; Sudirman, Sudirman; Berimah, Azizah Putri; Kurniawan, Ade (Jurnal Pendidikan MIPA, 2023)
Abstract: Hybrid classes is combination of face-to-face learning and online learning, where some students attend physical classes while other take lessons online. This research aims to produce a reflective micro-learning model in hybrid classes that is valid, practical and effective for prospective Physics teachers. modifications to the Plomp model produced reflective Micro Teaching tools based on hybrid classes in the form of RPS, SAP, teaching materials and assessment instruments. Based on the N-Gain value in the Pre-Test and Post-test results, the Offline learning mode is 0.0010 (0.1%) and Online is 0.0392 (3.92%) Judging from the N-Gain value category and Effectiveness Interpretation Category means both learning modes are in the low and ineffective category. Online learning using Phet Colorado media has a greater N-Gain value so it can be concluded that the online learning mode using Phet Colorado is more effective than the offline learning mode using equipment in the Physics Laboratory. Keywords: reflective micro learning, hybrid classes, micro teaching Abstrak: Kelas hibrida mengacu pada kombinasi pembelajaran tatap muka dan pembelajaran daring, di mana sebagian siswa hadir di kelas fisik sementara siswa lainnya mengikuti pelajaran secara daring. Penelitian ini bertujuan menghasilkan model pembelajaran mikro reflektif pada kelas hybrid yang valid, praktis, dan efektif untuk calon guru Fisika. Penelitian pengembangan dengan modifikasi model Plomp menghasilkan perangkat pembelajaran Micro Teaching reflektif berbasis kelas hybrid berupa RPS, SAP, bahan ajar dan instrumen penilaian. Berdasarkan nilai N-Gain pada hasil Pre-Test dan Post test moda pembelajaran Luring adalah 0,0010 (0,1%) dan Daring adalah 0,0392 (3,92%) Dilihat dari kategori nilai N-Gain dan Kategori Tafsiran Efektivitas N-Gain maka kedua moda pembelajaran berada pada kategori rendah dan tidak efektif. pembelajaran Daring dengan menggunakan media Phet Colorado memiliki nilai N-Gain yang lebih besar sehingga dapat disimpulkan bahwa moda pembelajaran daring dengan menggunan Phet Colorado lebih efektif dibandingkan dengan moda pembelajaran luring dengan menggunakan peralatan pada Laboratorium Fisika.  Kata kunci: mikro reflektif, kelas hybrid, pembelajaran mikro DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp710-716